Rural agro-tourism and local community income: the case study of clustered homestays in Kelantan and Terengganu - Bachok, Syahriah; Hasbullah, Hafizah; Tuan Mohd Amin, Tuan Anisdina (Malaysian Institute of Planners, 2019)
This research outlines the analysis of income generation basing on agro-cultural tourism of homestays under the purview of Ministry of Tourism and Culture of Malaysia. Using a case study of Kelantan and Terengganu, the research elaborates on the levels of income generated from agro-tourism, distributions, administrations, factors leading to the success of homestays in generating additional income and strategies of infrastructural improvements of homestay. Tourism is one of the largest contributing sectors (13%) to the National Gross Product (RM153 billion) in 2015. Agro-tourism provide opportunities for the visitors to stay and experience the life of an agriculture community in rural areas. Kelantan and Terengganu are rich with agricultural produce, thus have the advantage of showcasing the unique attractions to various tourists’ types. Homestays in Kelantan and Terengganu are limited in research. Hence, this research aims to assess the rural agro-tourism and local community income generated from homestays in Kelantan and Terengganu.